Transmission Raman Spectroscopic Quantification of Active Pharmaceutical Ingredient in Coated Tablets of Hot-Melt Extruded Amorphous Solid Dispersion. Issue 1 (January 2020) - Liu, Yemin; Doddi, Jayanth; Zheng, Yanbing; Ho, Vivien; Pheil, Maurice; Shi, Yi
Transmission Raman spectroscopy is an emerging technique, capable of quantitative analysis of drug products nondestructively using a multivariate data analysis approach. We developed and validated a chemometric method to quantify the active pharmaceutical ingredient in coated tablets of hot-melt extruded amorphous solid dispersion. A partial least squares regression (PLSR) model was developed and validated based on transmission Raman spectra data collected from coated tablet samples with variations in the content of active pharmaceutical ingredient, excipients, water content, a key oxidative degradant, milled extrudate particle size distribution, and tablet hardness. The method was proven to be accurate, linear, specific, and robust. Our work demonstrates that transmission Raman spectroscopy (TRS) is a viable, cost-effective, secondary method to high-performance liquid chromatography (HPLC) for quantitation of active pharmaceutical ingredient (API) in coated tablets of hot-melt extruded amorphous solid dispersion.